Embracing Big Data in Medical Education in Malaysia: Overcoming Challenges and Seizing Opportunities - Syahrul Nizam, Junaini; Chew, Keng Sheng (Universiti Putra Malaysia, 2023)
The increasing volume of data generated in the medical field presents both opportunities and challenges for medical education in Malaysia. On one hand, the data allows for the development of genomic and precision medicine (1). However, it also raises concerns about data ownership, potential hacking, and the lack of a centralized electronic the local medical record.